2020
DOI: 10.14710/mkmi.19.1.31-37
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberian Media Booklet Kesehatan Reproduksi terkait Cybersex (Studi di SMA Kabupaten Banyuwangi)

Abstract: Latar belakang: Materi seksual online yang semakin mudah untuk diakses dibandingkan dunia nyata membuat remaja menjadi konsumen setia cybersex. Penelitian di Jawa Timur menunjukkan hasil 76,8% penikmat cybersex ada pada usia 15 – 17 tahun. Tujuan penelitian untuk mengetahui pengaruh pemberian pendidikan kesehatan reproduksi terhadap pengetahuan, persepsi dan praktik remaja terkait cybersex.Metode: Jenis penelitian adalah Quasi Eksperimental dengan metode Pretest – Posttest Control Group Design terhadap 66 sisw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…About 60% of internet users visit sites or websites that are sexual in nature and 87% of students have virtual sex (Hendarto & Ambarini, 2019). According to survey data from the Ministry of Information and Communication (Yunita et al, 2020), ranking of porn site users in Indonesia in 2013 Indonesia was ranked sixth for porn site access, then in 2014 it increased to third place, and in 2015 to second place. Sexual cases involving school-age children continue to increase from year to year Ali & Asrori, (2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 60% of internet users visit sites or websites that are sexual in nature and 87% of students have virtual sex (Hendarto & Ambarini, 2019). According to survey data from the Ministry of Information and Communication (Yunita et al, 2020), ranking of porn site users in Indonesia in 2013 Indonesia was ranked sixth for porn site access, then in 2014 it increased to third place, and in 2015 to second place. Sexual cases involving school-age children continue to increase from year to year Ali & Asrori, (2006).…”
Section: Introductionmentioning
confidence: 99%
“…(Refwan, 2019). Research in East Java also shows the results of 76.8% of cybersex connoisseurs aged 15-17 years by watching porn on gadgets (Yunita et al, 2020). Based on a preliminary study on February 2022 at SMA Antartika 2 Sidoarjo, researchers conducted interviews with 10 class XI students and found that 100% of students said they had accessed pornographic films out of curiosity and then they searched for pornographic films on the internet.…”
Section: Introductionmentioning
confidence: 99%